Pemodelan dan Desian Kendali Torsi Menggunakan Metode Sistem Identifikasi Untuk Meningkatkan Kenyamanan Penumpang Pada Trem Otonom - Azarya Pramayudo; Arief Syaichu Rohman; Bambang Riyanto Trilaksono (JTRM (Jurnal Teknologi dan Rekayasa Manufaktur), 2026)
Trams are transportation vehicles that fall under the category of Light Rail Vehicles (LRV), operating in urban areas and connecting different regions within a large metropolitan environment. Tram tracks differ from conventional railways, as they typically consist of dedicated lanes located on or adjacent to roadways, often with specific barriers in place. This condition presents a new challenge, as autonomous trams must be able to adapt to this dynamic environment. This study aims to develop a control system that considers passenger comfort, particularly during braking or deceleration in specific situations and conditions. The System Identification method is chosen to analyze the system's real response to a given input, with the identification results used to design the controller. The identification results and control design were then tested using MATLAB to evaluate the performance of the designed control system in providing a comfortable deceleration experience for passengers. The design results indicate that the control system can regulate torque variations while maintaining acceleration and its rate of change within safe limits.